Design and Construction of a Website-Based Bus Ticket Booking Information System - Ichsan, Aulia (Universitas Islam Sumatera Utara, 2024)
In the business world, generally users and owners of companies need something innovative to help support performance and facilitate the use or search for product data. The presence of this website-based internet will make it easier for all groups to access all forms of information, including utilizing the media to be able to connect the relationship between customers and the company's products, namely one of which is ordering bus tickets. Based on the various conveniences and uses of the internet, a